-x+3+13x=-6+3x+54

Simple and best practice solution for -x+3+13x=-6+3x+54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+3+13x=-6+3x+54 equation:


Simplifying
-1x + 3 + 13x = -6 + 3x + 54

Reorder the terms:
3 + -1x + 13x = -6 + 3x + 54

Combine like terms: -1x + 13x = 12x
3 + 12x = -6 + 3x + 54

Reorder the terms:
3 + 12x = -6 + 54 + 3x

Combine like terms: -6 + 54 = 48
3 + 12x = 48 + 3x

Solving
3 + 12x = 48 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
3 + 12x + -3x = 48 + 3x + -3x

Combine like terms: 12x + -3x = 9x
3 + 9x = 48 + 3x + -3x

Combine like terms: 3x + -3x = 0
3 + 9x = 48 + 0
3 + 9x = 48

Add '-3' to each side of the equation.
3 + -3 + 9x = 48 + -3

Combine like terms: 3 + -3 = 0
0 + 9x = 48 + -3
9x = 48 + -3

Combine like terms: 48 + -3 = 45
9x = 45

Divide each side by '9'.
x = 5

Simplifying
x = 5

See similar equations:

| 18y=9y+18 | | 5(x-4)+4(x-6)=7 | | 2-x+5=7-3 | | 5x+4+26=90 | | -x+2+7x=-2+2x+16 | | N^2+6n-21=0 | | 5m-4=2m-22 | | 22x+22(x-9)=45 | | 6v+2v+3= | | x^4+72x^2+94400=0 | | 2(4)+p=35 | | -16t(t+1)(t-5)=0 | | 2x+4(x-5)=2(x-4) | | 8m-11+2m-4=180 | | -x+3+14x=-6+4x+36 | | 2x+6-x-3=40 | | 0.09x+0.19(x+7000)=3570 | | (3x-3)=48 | | 3x^2-2y=48 | | (3x-3)=58 | | 2x^2+3x-23=3 | | 5b-22=7b+12 | | 4x-5(2x+1)=6x+1 | | 4x-5(2x+1)=-6x+5 | | 0.3(x+-100000)=1000000 | | 4x-5(2x+1)=1x+-5 | | 38ln(x)=79 | | 38lnx=79 | | 4x-5(2x+1)=0x+-5 | | -(3x-5)-(5x-2)+4=-8(x-4)-(3x+4)+4 | | 4x-5(2x+1)=-0x+-5 | | x^2y+4y+5x^2+20= |

Equations solver categories